The impact of caffeine-mediated gut microbiota regulation on the athletic performance of football players - Yang, J.; Zhu, H.; Yao, B.; Zhang, W.; Xing, X.; Cheng, W.; Dong, C. (Biology of Sport, 2026)
Caffeine is widely utilized as an ergogenic aid in sports, yet its interaction with gut microbiot — a key modulator of metabolic and physiological processes — remains underexplored in athletic populations. This study aimed to investigate whether caffeine supplementation enhances the athletic performance of football players through gut microbiota regulation, thereby bridging the gap between caffeine`s ergogenic effects and microbial mediation mechanisms. A 7-day randomized, double-blind, placebo-controlled trial was conducted with 32 male national-level football players. Participants were allocated to either a caffeine group (3 mg/kg body mass) or a placebo group. Performance assessments included agility tests, 30-m repeated sprints, technical dribbling tasks, and aerobic endurance evaluations. Fecal samples were analyzed via 16S rRNA sequencing to assess microbial diversity and composition. Structural equation modeling (SEM) was employed to evaluate the mediating role of gut microbiota. Caffeine supplementation significantly improved agility (p < 0.001, Cohen`s d = 1.1), sprint performance (p = 0.007, d = 0.7), and technical execution (p = 0.003, d = 0.7) compared to placebo. Gut microbiota alpha diversity (Chao1, Shannon) increased in the caffeine group (p < 0.05), with enrichment of Prevotella, Bacteroides, and Veillonella. SEM revealed that 33.3% of caffeine`s performance-enhancing effect was mediated by microbial diversity (* = 0.2, p = 0.01), while no direct caffeine-performance pathway was observed (p = 0.2). These findings demonstrate that caffeine enhances football-specific performance partially through gut microbiota modulation, emphasizing the microbiome`s role in translating nutritional interventions into athletic gains. Future research should explore long-term microbial adaptations and personalized strategies combining caffeine with microbiome targeted therapies.